THE INFLUENCE OF LOCUS OF CONTROL, PRIVATE SUPPORT AND COMMUNITY STIGMA ON HIVAIDS INFECTION PREVENTION PLWHA IN KDS FRIENDSHIP PLUS KEDIRI - Sukowati, Via Nikitasari; Sari, Nia; Sari, Ema Maya (Universitas STRADA Indonesia, 2019)
WHO information the incidence of HIV / AIDS tends to increase from year to year. This shows that efforts to prevent transmission of HIV/AIDS to PLWHA are also less effective. The purpose of this study was to determine the effect and which are the most influential between LoC, peer support and community stigma on efforts to prevent the transmission of HIV/AIDS in PLHIV in KDS Friendship Plus Kediri. Design of quantitative analytic research with cross sectonal approach. The population is PLWHA members of KDS Friendship Plus Kediri with a sample of 30 respondents by Accidental Technique. Collection uses questionnaire and is analyzed by linear regression. The results showed that there was an influence of LoC on efforts to prevent HIV / AIDS transmission (p value 0.004 <0.05), there was an influence of peer support on efforts to prevent HIV / AIDS transmission (p value 0.006 <0.05), and there was an influence of community stigma on efforts to prevent HIV/AIDS transmission (p value 0.044 <0.05). The variables that most influence efforts to prevent HIV / AIDS transmission in PLWHA are peer support variables using multiple linear regression analysis with results (B = 0.233) this occurs because peer groups are groups that can be accepted by PLWHA, understand the needs of PLWHA, and closest to giving motivation for PLWHA